Contextual factors shaping the design of last-mile delivery business models - a case for Swedish logistic service providers - Christensen,Cecilie Vang; Lindén,Emma (2023)
Purpose: This thesis aims to strengthen the understanding of contextual business model design within the last-mile delivery industry and create a foundation for transferable knowledge from which Swedish logistic service providers can draw knowledge connected to last-mile delivery business models from. Theoretical framework: The theoretical framework is a decision-making process model, illustrating the most salient contextual factors to business model design for logistic service providers. It consists of a series of external factors and internal factors identified through the empirical data. Methodology: Qualitative multiple-case study with an abductive research approach. Empirical foundation: The data was collected through seven semi-structured interviews with participants from three case companies and the expert side of the last-mile delivery industry. A documentary review was conducted to complement and strengthen the primary data. Findings: The research found that both internal and external factors play a significant role in the business model design choices that logistic service providers make. External factors influence what business models companies adopt, prompting them to design sustainable and emerging business models. The internal factors were found not to impact what business models are adopted, but rather how business model portfolios are designed. This was identified to affect the number and diversity of business models in the company’s portfolio, leading to either diversification or a single operating business model. Contribution: We are contributing to academia by addressing the fragmentation of literature on last-mile delivery business model design. This is done by providing deeper insights into the impact that contextuality has on business model design itself and suggesting the importance for having a comprehensive and holistic view of both the internal and external company contexts. It specifically contributes with and calls for recognition of the importance of internal factors.
Keywords: Last-mile delivery; Logistic service providers; Business model; Business model design; Decision-making; Internal environment; External environment